A Comparative Study on Activated Carbons Derived from a Broad Range of Agro-industrial Wastes in Removal of Large-Molecular-Size Organic Pollutants in Aqueous Phase - Cruz, GJF (2015)
The National University of Tumbes provided important financial support (Proyecto de Investigacion Docente - Resolucion No 1217-2013/UNT-R). The Academy of Sciences of the Czech Republic and Consejo Nacional de Ciencia, Tecnologia e Innovacion Tecnologica (CONCYTEC) in Peru (joint project reg. No. 002/PE/2012) are also gratefully recognized for their support. The Academy of Finland and the Finnish Funding Agency for Innovation (Tekes) are acknowledged for research funding to the AdMatU project from the Development funds and to the HYMEPRO project, respectively. Thanks to Dr. Gladys Ocharan, Alex Diamond, and Hana Snajdaufova (from ICPF) for technical support and Dr. Tomas Strasak (from ICPF) for help with DFT calculations.